Good governance and local government in post-war sri lanka: a case study of navithanveli predhesiya sabah - Fowsar, M.A.M. (University of Jaffna, 2012)
Good Governance is widely considered to be a necessary and important concept if a country or province or region or division is to develop politically, socially and economically during the post-war context. While good governance might be taken as a given right in most western parts of the world because of its basic principles it has not proved to have the same impact on other parts of the world. In the present context, the strength of local government depends therefore on its basis in good governance and from that basis it gains its legitimacy. Only if local government has a strong basis in good governance can it have a legitimate claim to a major and distinctive role in any central government. On this backdrop, this study focuses on the crisis of good governance in Navithanveli Predhesia Sabah of Eastern Province of Sri Lanka. The prime objective of this study is to give a brief account of the political and development role of council since it established. Meanwhile, it scrutinizes the decision-making process along with the achievement which has been gained through good governance in the study area. The fundamental question of the research is what conditions enable a better government to generate the capabilities that transform it into successful democratic governance, and how to generate them? Such questions are the central points of this research. All such inquiries are analyzed in this study from theoretical perspectives and factual findings. Several approaches are employed to analyse and interpret social phenomena. This study is based on interpretative approach. The data for the study have been collected from both primary and secondary sources of information. The study reveals that the council has become marginalized and insignificant in the public eye.
Keywords: Good governance; Local government; Post-war